SPRINTERS’ TRAINING WORKLOAD AND REST PATTERNS - Maslennikov, Alexander Valeryevich; Vakalova, Lyudmila Georgievna; Zayko, D mitry Sergeevich; Dmitriev, Igor Viktorovich; Voinova, Svetlana Evstafievna; Mironov, Alexander Alekseevich (International Journal of Psychosocial Rehabilitation, 2020)
Athlete’s training level and high athletic performance are achieved by multiple repetitions of training loads that are differing in volume and intensity. Therefore, to build a sports training program correctly and rationally is to find the optimal intervals between repeated workouts in the training process, in other words, to find the criterion of optimal readiness for the subsequent exercise performance, training session or participation in the competition. The available data on the problem under study are unsystematized and fragmented in the scientific and methodological literature. This issue was the relevant line of our research. However, the issue of the rational alternation of physical exercises in various types of athletics, as applied to short distance running, has not yet received a sufficiently complete scientific justification. This factor served as the basis for the purpose of our study: to determine the optimal combination of patterns of alternating run segments with rest, which contributes to the development of running speed and speed endurance in sprinters. Studying this issue will contribute to the further study of sprint training techniques. Therefore, to answer the research goal, the following tasks were formulated: to generalize the data of the scientific and methodological literature on the influence of various patterns of training and rest on the change in special working capacity and functional state in sprint; to determine the influence of optimal load and rest regimens on the improvement of speed and speed endurance in short distance running. The practical significance of the study lies in determining the optimal load and rest alternation patterns, which affect the change in the functional capabilities of the sprinter during the development of the required physical qualities. The theoretical significance is concerned with updating and adding the latest data to theoretical provisions regarding the problem of training regimens and the workload intensity on the improvement of speed and speed endurance in short distance running.